Why Trade Facilitation Matters to Africa - Portugal-Perez, Alberto (2012)
Mitigating the impact of the economic crisis will require using all the tools necessary to regain a sustainable path to growth. This includes measures to support trade expansion, including in developing countries, such as those in Africa. This paper provides context for understanding why trade facilitation and lowering trade costs matter to Africa both today and over the long term. Trade costs are higher in Africa than in other regions. Using gravity-model estimates, the authors compute ad-valorem equivalents of improvements in trade indicators for a sample of African countries. The evidence suggests that the gains for African exporters from cutting trade costs half-way to the level of Mauritius has a greater effect on trade flows than a substantial cut in tariff barriers. As an example, improving logistics so that Ethiopia cuts its costs of trading a standardized container of goods half-way to the level in Mauritius would be roughly equivalent to a 7.6% cut in tariffs faced by Ethiopian exporters across all importers.